1999
DOI: 10.2136/sssaj1999.634999x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phosphorus Soil Test Extractants for Plant Availability and Environmental Assessment

Abstract: A number of soil tests have been proposed to predict crop response to added P or to assess potential for soil P loss to runoff waters. A series of four separate experiments were conducted over a 10‐yr period to evaluate soil test methods on a total of 163 Vermont and New York field soils. The experiments included the following: (i) a pot study with alfalfa grown in the greenhouse with 31 soils either unfertilized or fertilized with 18 mg P kg−1; (ii) routine chemical analysis on 54 soils; (iii) a 360‐d incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
3
54
0
1
Order By: Relevance
“…tightness of relations between P ex and phosphates estimated with the Mehlich 3 and Doppel-lactat methods shows that these methods probably did not estimate significant contents of nonbioavailable P. Significant relations between P M3 and P ex were obtained in the work of Zheng et al (2003). Close correlations between P in soil solution and P M3 was also found by Magdoff et al (1999), who reached r = 0.8 at P ≤ 0.01 in 28 noncalcareous soils. Zbíral and němec (2002) compared the P M3 and P CaCl 2 fractions using regression analysis and obtained significant relations as well (coefficient of determination r 2 = 0.56).…”
Section: Methodsmentioning
confidence: 89%
“…tightness of relations between P ex and phosphates estimated with the Mehlich 3 and Doppel-lactat methods shows that these methods probably did not estimate significant contents of nonbioavailable P. Significant relations between P M3 and P ex were obtained in the work of Zheng et al (2003). Close correlations between P in soil solution and P M3 was also found by Magdoff et al (1999), who reached r = 0.8 at P ≤ 0.01 in 28 noncalcareous soils. Zbíral and němec (2002) compared the P M3 and P CaCl 2 fractions using regression analysis and obtained significant relations as well (coefficient of determination r 2 = 0.56).…”
Section: Methodsmentioning
confidence: 89%
“…Also, soluble organic C from BL may compete with orthophosphates for anion adsorption sites thus reducing the potential sorption capability. [15,39,40] The lower amounts of extractable P in the Corozal soil as compared to the San Anto´n soil for all treatments is probably due to an increase in the magnitude of sorption and precipitation reactions due to its oxidic and kaolinitic mineralogy. In the San Anto´n soil, extractable P increased with increasing amounts of P added as TSP after one week of incubation.…”
Section: Phosphorus Availability As Function Of Timementioning
confidence: 98%
“…The ODS samples were prepared for the assessment of available P using the following methods: (i) available P was extracted using Mehlich-1 Pavan et al (1992); (ii) available P was extracted using the ion exchange resin method (P-IER): [Amberlite IRA-410 and Amberlite IRA-120], following Raij, Quaggio, and Silva (1986); and (iii) available P was Magdoff et al (1999).…”
Section: Claymentioning
confidence: 99%
“…On the other hand, one of the critiques of the IER method has been the low practicality of the method, complicating its large-scale use (MOREIRA;MALAVOLTA, 2001). Therefore, it is interesting to study other P extraction methods, for example, the modified Morgan (MM) solution, suggested by Magdoff et al (1999). That method has been used in the United States and has high extraction capacity for P linked to the organic fraction of the soil, which is significant in soils under NT (RHEINHEIMER;ANGHINONI, 2003).…”
Section: Introductionmentioning
confidence: 99%